Asociación entre percepción de consumo de sal e hipertensión arterial en pobladores peruanos. - Failoc-Rojas, V.E. (2019)
Introduction: Non-pharmacological control of hypertensive patients should be evaluated as it has been shown to be beneficial along with pharmacological treatment. It is not known how is self-perception of salt consumption in Peruvian hypertensive groups. Objective: To determine the association between perception of salt consumption in the diet and arterial hypertension in Peruvian residents. Methods: Analytical cross-sectional study, through the interview of self-reported data on the perception of salt consumption and the diagnosis of arterial hypertension, as well as other co-variables of interest. Prevalence ratios (PR) were estimated using generalized linear models, Poisson family, and using the city as a cluster. Results: Of 4263 participants, 63.1% were women and the median age was 42 years. 53.3% said they consumed regular or a lot of salt in their diet. In multiple regression, there was a positive association between the perception of salt consumption and arterial hypertension (RP: 1.56, 95% CI: 1.29-1.89, p <0.001). Age was also positively associated in years (RP: 1.03, 95% CI: 1.03-1.04, p <0.001), underweight (RP: 1.51, 95% CI: 1.24-1.84, p <0.001) and overweight (RP: 2.29, 95% CI: 1.80-2.92, p <0.001), suffer from diabetes (RP: 1.36, 95% CI: 1.14-1.61, p <0.001) and hypercholesterolemia (RP: 1.56, 95% CI: 1.40-1.75, p <0.001). Female sex (RP: 0.91, 95% CI: 0.83-0.99, p = 0.027) and Chinese race (RP: 1.72e-05, 95% CI: 2.36e-06-1.25e-04, p <0.001) were negatively associated . Conclusion: More than half perceived regular or high salt intake in their diet but the prevalence of hypertension was low. The perception of low salt intake was frequent in the hypertensive group.